Implementasi Metode PSI (Preference Selection Index) pada Penjualan Alat Komputer Berbasis E-Commerce Toko DMC Computer - Gerry Alfaro Christof Mone; Skolastika Siba igon (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
In today's digital era, E-commerce is growing rapidly and provides convenience for customers in online shopping, including in the purchase of computer equipment. However, the large number of product choices often makes it difficult for customers to determine the best choice according to their needs and preferences. Therefore, this research aims to implement the Preference Selection Index (PSI) method in the E-commerce system at DMC Computer store to help customers make the best product choices based on various criteria, such as price, specifications, brand, and customer reviews. The PSI method is used because of its ability to rank alternatives based on user preferences objectively. The results of this study show that the developed system can increase efficiency in the product selection process and provide more accurate recommendations for customers. Thus, the implementation of the PSI method in E-commerce can be an effective solution in improving customer shopping experience as well as store competitiveness in the E-commerce industry. Hopefully, this research can be a reference for the development of E-commerce systems that are more intelligent and responsive to customer needs. In addition, it is hoped that the implementation of the PSI method can continue to be developed and applied more widely in various industrial sectors to improve efficiency in the decision-making process and customer satisfaction.